Removal of hydrogen sulphide using hydrogel biochar derived from coal fly ash through multi sorption bed / Muhammad Ridhauddin Mohd Said - Mohd Said, Muhammad Ridhauddin (2017)
Nowadays, great effort has been done on the finding of the utilization of coal fly ash. This is because the amount of coal fly ash generated annually is enormous and has become quite a concern because if it is not disposed properly it might bring a lot of problem to the environment. The objectives of this study were to produce hydrogel biochar coal fly ash (HBC-CFA), study the characteristics of the hydrogel produced, study its efficiency on H2S removal and compare it with hydrogel produced from the biochar of empty fruit bunch. The HBC-CFA was prepared by using several materials which were acrylamide (AAm) as the monomer, N, N‟- Methylenebisacrylamide (MBA) as the crosslinker and Ammonium Persulphate (APS) as the initiator and raw coal fly ash itself. Analysis equipment that were used in the characterization of HBC-CFA were Thermogravimetric Analyzer (TGA) to study the proximate properties, Elemental Analyzer (EA) to study the ultimate properties, Brunaeur-Emmett Teller (BET) to study the surface area and Scanning Electron Microscopy (SEM) to study the morphology. For the study on its efficiency of H2S removal two parameters have been chosen which were the effect on bed loading and the effect of wetness. The number of bed used for adsorption was varied from 1 to 3 to study the effect of loading while 3 wet beds loading have been used to study the effect of wetness. For the study on bed loading, 3 beds loading recorded the most H2S gas adsorption with 209ppm adsorption value while for the study on wetness, wet bed recorded the most H2S gas adsorption with 241ppm adsorption value. The study on the comparison on chracteristics between HBC-CFA and HBC-EFB showed that the HBC-CFA has higher surface area, pore volume and smaller pore diameter which were a good characteristics for and adsorbent. However, HBC-EFB has higher efficiency in H2S removal than HBC-CFA. The recorded value for 3 beds loading for HBC-EFB is 241ppm while for wetness is 262ppm. Both values are higher compared to HBC-CFA. The percent of H2S removal were ranging from the lowest which was 46% to the highest which was 66%.